(untitled) (Journal of Population and Development, 2022)
This research paper examines the contribution of remittance on socio-economic development of Nepal. The specific objectives are to study the trends, patterns and diversifications of foreign labor migration. This study uses entirely secondary data. The majority of Nepali families earn their income through foreign employment. Nepal has about 200 years’ long history of receiving international remittance, as a sum of money transferred from foreign migrant workers to individual or their families in their homeland. The Gulf Cooperation Council and Malaysia are the major destination countries for Nepalese workers. The report of National Planning Commission 2020/21 shows Nepal received NPR 961.05 billions remittance from 128 different countries constituting 22.5 percent of the Gross Domestic Product (GDP). The report of economic survey 2020/21 shows annual per capita income of Nepal reached 1, 381 US dollars in 2021, with an increment of about 11 percent to the previous year. Migration and remittance have contributed to increase the per capita income of Nepal over the years along with significant change in the social development.